Cryo-Milled β-Glucan Nanoparticles for Oral Drug Delivery - Guanyu Chen; Yi Liu; Darren Svirskis; Hongyu Li; Man Ying; Weiyue Lu; Jingyuan Wen (MDPI AG, 2024)
Gemcitabine is a nucleoside analog effective against a number of cancers. However, it has an oral bioavailability of less than 10%, due to its high hydrophilicity and low permeability through the intestinal epithelium. Therefore, the aim of this project was to develop a novel nanoparticulate drug delivery system for the oral delivery of gemcitabine to improve its oral bioavailability. In this study, gemcitabine-loaded β-glucan NPs were fabricated using a film-casting method followed by a freezer-milling technique. As a result, the NPs showed a small particle size of 447.6 ± 14.2 nm, and a high drug entrapment efficiency of 64.3 ± 2.1%. By encapsulating gemcitabine into β-glucan NPs, a sustained drug release profile was obtained, and the anomalous diffusion release mechanism was analyzed, indicating that the drug release was governed by diffusion through the NP matrix as well as matrix erosion. The drug-loaded NPs had a greater ex vivo drug permeation through the porcine intestinal epithelial membrane compared to the plain drug solution. Cytotoxicity studies showed a safety profile of the β-glucan polymers, and the IC50s of drug solution and drug-loaded β-glucan NPs were calculated as 228.8 ± 31.2 ng·mL−1 and 306.1 ± 46.3 ng·mL−1, respectively. Additionally, the LD50 of BALB/c nude mice was determined as 204.17 mg/kg in the acute toxicity studies. Notably, pharmacokinetic studies showed that drug-loaded β-glucan NPs could achieve a 7.4-fold longer T1/2 and a 5.1-fold increase in oral bioavailability compared with plain drug solution. Finally, in vivo pharmacodynamic studies showed the promising capability of gemcitabine-loaded β-glucan NPs to inhibit the 4T1 breast tumor growth, with a 3.04- and 1.74-fold reduction compared to the untreated control and drug solution groups, respectively. In conclusion, the presented freezer-milled β-glucan NP system is a suitable drug delivery method for the oral delivery of gemcitabine and demonstrates a promising potential platform for oral chemotherapy.